Sustainable agriculture and Islamic finance: cultivating prosperity and values - Mohd Zain, Nor Razinah; Tounchibine, Oumaima; Lechheb, Houda (Emerald Publishing Limited, 2024)
Agriculture is one of the oldest socio-economic activities. It involves growing valuable plants and animals for human existence. Sustainable agriculture should be understood in light of the global sustainable development movement, which emphasizes balancing environment, society and economics. With the ongoing effects of the COVID-19 pandemic and the recent war between Russia and Ukraine, sustainable agriculture can help eliminate food insecurity caused by food shortages and agricultural sector disruptions. Recently, investors, practitioners, academicians, researchers, regulators and financiers are increasingly interested in using Islamic financing products and qualified Shariah-compliance contracts to promote sustainable agriculture. Many Organization of Islamic Cooperation (OIC) states still rely on agriculture for socioeconomic growth. These countries are major contributors to Islamic financial growth. This study assesses Islamic finance’s role in promoting sustainable agriculture in selected OIC countries. The researchers use qualitative methods and meta-analysis data to determine the constraints and benefits of implementing Islamic financial products for sustainable agriculture. This study suggests that OIC state governments should promote sustainable agriculture. OIC member states have different achievements relating to their sustainable agriculture. Based on socio-economic factors, agriculture policies or plans, leadership and political will, Islamic finance products and Shariah-compliance contracts are found underutilized in meeting sustainable agriculture and sector stakeholders’ needs. A solid Islamic financial framework for sustainable agriculture, good governance and improved agriculture policy are needed.